MODERN METHODS OF COMPETENCE BUILDING APPROACH IMPLEMENTATION IN THE SYSTEM OF TRAINING SPECIALISTS IN HIGHER EDUCATIONAL ESTABLISHMENTS - E. G. Gutsu (Вестник Мининского университета, 2017)
The article discusses a problem of the changing of requirements of professional competence of teacher of university connected with transition to a competence model of professional education. The article tackles upon the problem of using the portfolio method in the process of the article introduces the short review of such notions as: forms and different variants of using methods. Besides, the author of the article points out the use of the portfolio method in the training of the specialists (social teachers, teachers of primary school) during the whole process of studying at the Pedagogical Institute.